LONGEVITY ASSOCIATED VARIANT OF BPIFB4 MITIGATES MONOCYTE MEDIATED ACQUIRED IMMUNE RESPONSE. (16th November 2018) - Villa, F; Ciaglia, E; Maciag, A; Montella, F; Ferrario, A; Cattaneo, M; Puca, A
Abstract: One of the basis of exceptional longevity is the maintaining of the balance between inflammatory and anti-inflammatory networks. The monocyte-macrophages activation plays a major role in tuning the immune responses, by oscillating between patrolling-protective to inflammatory status. Longevity-associated variant (LAV) of bactericidal/permeability-increasing fold-containing-family-B-member-4 (BPIFB4) activates calcium, PKC-alpha and eNOS, rescuing endothelial dysfunction in aged mice and inducing revascularization. The BPIFB4's increment in serum of healthy long-living individuals (LLIs) compared to non-healthy ones, its therapeutic potential in improving vascular homeostasis, which depends on immune-system, together with its expression in bone marrow myeloid cells, suggests that LAV-BPIFB4 may improve immune-regulation. Here we show that human monocytes exposed to LAV-BPIFB4 protein increased co-stimulatory molecules in resting state and reduced pro-inflammatory cytokine TNF-α and IL-1β after activating stimuli. Accordingly, a low percentage of CD69+ activated-lymphocytes are found among LAV-BPIFB4-treated Peripheral Blood Mononuclear Cells (PBMCs). Moreover, human monocyte-derived dendritic cells (DC) generated in presence of LAV-BPIFB4 secreted higher anti-(IL-10 and TGF-β) and lower pro-inflammatory (TNF-α and IL1β) cytokines. Accordingly, LLIs's plasma showed higher levels of circulating IL-10 and of neutralizing IL-1RA compared to controls. Thus, LAV-BPIFB4 effects on myeloid compartment could represent one example of a genetic predisposition carried by LLIs to protect from immunological dysfunctions.